Anti-Inflammatory Effects of Miang Bean Leaves (Mucuna pruriens) - Fadilaturahmah Fadilaturahmah; Firman Syukri; Yona Afriani; Putra Santoso (Journal of Tropical Pharmacy and Chemistry, 2022)
Inflammation is a serious health problem that needs treatment. The use of steroids and non-steroidal anti-inflammatory drugs (NSAIDs) can actually relieve inflammatory reactions well, but their long-term use can have many side effects and are uneconomical. Therefore, the use of natural ingredients that are effective and economical is needed. One of the plants that are considered anti-inflammatory is the leaves of miang beans (Mucuna pruriens). The purpose of compiling this narrative review is to analyze the phytochemical content of miang beans leaves and its mechanisms for inflammatory reactions. The narrative study of this preparation was carried out using the literature study method from August to September 2020. The phytochemical content of miang bean leaves are alkaloids, flavonoids, saponins, cyanogenic glycosides, and tannins. Phytochemicals that have a direct anti-inflammatory effect are alkaloids, flavonoids, saponins, and tannins. Alkaloids are antibacterial. If there are bacteria that cause inflammation, the alkaloids will damage the bacterial peptidoglycan cell walls, thus causing bacterial cell death and preventable inflammatory reactions. Flavonoids have anti-inflammatory effects by inhibiting macrophages from producing NO (nitric oxide) and inhibiting the cyclooxygenase pathway. Saponins affect the inflammatory reaction by inhibiting the lipoxygenase pathway and inhibiting the release of inflammatory mediators. Meanwhile, tannins affect the inflammatory reaction by inhibiting macrophages from producing ROS (Reactive Oxygen Species). Potential which is fatal because it can turn into cyanide acid. However, the content of these cyanogenic glycosides can be minimized by drying at low temperatures. So, mung bean leaves are effective as anti-inflammatory drugs because the alkaloids, flavonoids, saponins, and tannins they contain are anti-inflammatory.